The enlarged perivascular spaces in the hippocampus is associated with memory function in patients with type 2 diabetes mellitus - Peichun Pan; Dongsheng Zhang; Jing Li; Min Tang; Xuejiao Yan; Xin Zhang; Man Wang; Xiaoyan Lei; Xiaoling Zhang; Jie Gao (Scientific Reports)
Abstract Early detection of cognitive dysfunction in patients with type 2 diabetes mellitus (T2DM) is important for preventive measures due to the lack of effective treatments. The purpose of this study is to investigate the relationship between enlarged perivascular space in the hippocampus (H-EPVS) and cognitive performance in patients with T2DM, and to determine whether it can serve as an imaging marker for cognitive dysfunction. 66 T2DM patients with cognitive impairment (T2DM-CI) and 71 T2DM patients with normal cognitive function (T2DM-NC) underwent cranial MRI scans and comprehensive neuropsychological assessments. H-EPVS counts were visually calculated on T2WI imaging according to a previous scale. The differences in the counts of H-EPVS, demographic data, laboratory test results, and cognitive assessment scores between the two groups were compared. The partial correlation analysis was used to explore the relationship between H-EPVS and glymphatic system function (indicated by the DTI-ALPS index), as well as markers of CSVD. Multiple linear regression models were conducted to explore the association between H-EPVS and cognitive functions. Compared with the T2DM-NC group, T2DM-CI exhibited significantly higher counts of H-EPVS in both the total (sum of the left and right side) and left side (P < 0.001). The T2DM-CI group had lower DTI-ALPS index and RAVLT total score. The total H-EPVS counts were significantly correlated with the DTI-ALPS index (r = − 0.240, P = 0.005), BG-EPVS (r = 0.325, P < 0.001), and CSO-EPVS (r = 0.183, P = 0.033). Multiple linear regression showed the total H-EPVS counts exhibited a negative correlation with MMSE (β = − 0.324, 95% CI: − 0.091, − 0.320), immediate memory (β = − 0.380, 95% CI: − 0.673, − 1.766) and delayed recall (β = − 0.252, 95% CI: − 0.052, − 0.463). H-EPVS may serve as a potential neuroimaging biomarker for cognitive impairment in patients with T2DM, warranting further investigation and validation in future studies.